Online Training: An Alternative Solution of the Empowerment for Parents of Children with Autism - Herlina, Herlina; Susilana, Rudi (Universitas Pendidikan Ganesha, 2021)
Parents need to understand how important it is to provide proper treatment in dealing with children with autism. The effort is with an intervention approach technique, but some parents often experience difficulties in making intervention efforts. One solution to the problem that can be done is by establishing the Independent Intervention Program Online Training (PIM). This study aims to prove that the Independent Intervention Program Online Training or PIM is an effective way to empower parents in dealing with children with autism. The research was conducted through field trials involving 11 parents of children with autism from a number of cities in Indonesia. Subjects were provided PIM Online Training by platforms such as Zoom, Website, and WhatsApp. Training effectiveness data is seen from the results of the subject's self-evaluation before and after training. The results showed that after participating in the PIM Online Training, parents saw themselves better in understanding the concept of Autism Spectrum Disorder (ASD), social skills, intervention, and individual intervention programs, as well as skills in designing intervention programs for children with disabilities. autism, compared to pre-training conditions. Based on these results, PIM Online Training is expected to be the right solution to empower parents in designing social skills intervention programs for children with autism, without limitation of time, place and cost.